Skin Cooling to Reduce the Pain Associated with Local Anesthetic Injection; a Randomized Controlled Trial - Majidinejad, Saeed; Heidari, Farhad; Chitgarian, Amir (Archives of Academic Emergency Medicine, 2022)
Introduction: Different methods have been proposed for the reduction of the pain caused by the injection of local anesthetics. This study aimed to evaluate the effect of skin cooling on reduction of pain associated with local injection of lidocaine buffered with sodium bicarbonate. Methods: This randomized controlled trial included 108 adult patients with arm/forearm wounds who referred to the emergency departments. Participants were randomly allocated to two equal groups. Patients in both groups received subcutaneous injection of buffered lidocaine. In the intervention group, an ice cube measuring 2 × 2 × 2 cm (at 0 ° C) in sterile gloves were placed on the wound for 2 minutes before the injection of buffered lidocaine. The primary outcome was severity of pain during lidocaine injection using a visual analog scale (VAS). Results: One hundred and eight patients were enrolled in the study, 54 in each group. There was no statistically significant difference in age (p = 0.777), sex (p = 0.466), and length of laceration (p = 0.410) between the two groups. The pain scores during lidocaine injection were significantly lower in the intervention group compared to control group (2.39 ± 1.14 vs 4.26 ± 0.94, p < 0.001). Conclusions: Skin cooling prior to the injection of local anesthetics can significantly reduce the pain caused by local anesthetic infiltration